PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS ANDROID BERBANTUAN KODULAR - Beideh, Beideh; Wijayanti, Rica (SIGMA, 2024)
The aim of this research is to produce and understand the process of developing Android-based mathematics learning media using a code using the ADDIE model, as well as producing Android-based mathematics learning media that is suitable for use by students. The method used in this research is the research and development (R&D) method using the ADDIE development model. research results and conclusions. The results of this research show that the Android-based mathematics learning media with the help of modular is said to be very feasible, based on the results of two expert validations, namely media experts and material experts who got an average score of 94%, which means it can be used with slight revisions. Learning media is said to be practical based on the results of the response questionnaire from 2 mathematics teachers who got a score of 88.35% and student responses got a score of 79.42% with the criteria being very feasible and practical to use..